A matter of style: The causes and consequences of style drift in institutional portfolios - Russ Wermers (University of Cologne, Centre for Financial Research (CFR), 2012)
The equity style orientation of an institutional portfolio has a large influence on its yearly returns. This paper analyzes the causes and consequences of portfolio style drift among U.S. equity mutual funds by developing new portfolio holdings-based measures of drift. These holdingsbased measures allow a decomposition of style drift into components that result from active versus passive portfolio decisions by a fund manager in three different equity style dimensions: size, bookto-market, and price momentum. We find that a significant amount of style drift results from active manager trades, therefore, managers that trade more frequently tend to manage portfolios with greater style drift. In addition, managers of growth-oriented funds and small funds, and managers having good stockpicking track records, tend to have higher levels of style drift than other managers; these managers also deliver better future portfolio performance as a result of their trades, even after accounting for their higher trading costs. Consistent with this superior performance, managers do not seem to be concerned with controlling style drift; indeed, managers tend to be style chasers during most years, which appears to benefit their performance. Overall, our findings suggest that controlling the style drift of a fund manager does not necessarily result in higher performance for investors.
Keywords: 330